Polycystic Ovary Syndrome – A Clinical and Psychosocial Perspective - Strzałkowska, Paulina; Mazur, Aleksandra; Dulęba, Julia; Sajewicz, Krzysztof; Tudaj, Oskar; Kaźmierczak, Monika; Kalas, Wiktoria; Kalisiak, Julia; Koszałko, Joanna; Kin, Filip (Quality in Sport, 2025)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrinopathies among women of reproductive age, characterized by a complex etiology and diverse clinical presentation. The aim of this paper is to present the current state of knowledge regarding the definition, diagnostic criteria, and differential diagnosis of PCOS, as well as to discuss treatment methods—both non-pharmacological and pharmacological. Particular attention is given to psychological aspects, which are often overlooked in clinical practice, despite their significant impact on the course of the disease and the quality of life of affected women. Women with PCOS more frequently experience depressive and anxiety disorders, along with low self-esteem, which can substantially hinder effective treatment and worsen prognosis. This paper emphasizes the need for a holistic approach to PCOS patients, taking into account not only somatic symptoms but also psychological and emotional needs, as a prerequisite for effective and long-term therapy.